#### Answer

$n$

#### Work Step by Step

$\binom{n}{n-1} =\dfrac {n!}{\left( n-1\right) !\left( n-\left( n-1\right) \right) !}=\dfrac {n!}{\left( n-1\right) !\times 1!}=\dfrac {n!}{\left( n-1\right) !}=n$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$n$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.